Battered lives a comparative content analysis of news stories on Filipina domestic workers in the Philippine Daily Inquirer, Manila Bulletin, and Philippine Star from January 2010 to December 2012 - Miranda, Jacqueline Portunes; Valentin, Francis Anthony Toledo (2013)
"This study examined how the three major Philippine dailies, namely the Philippine Daily Inquirer, Manila Bulletin, and Philippine Star, presented the news stories on Filipino domestic workers from January 2010 to December 2012. All the news articles gathered involving Filipina domestic workers both here and aborad within the given time frame were analyzed through content analysis and evaluated in terms of emphasis, balance, tone, and frames of focus. The Philippine Daily Inquirer and Philippine Star published more comprehensive news stories than Manila Bulletin. In terms of news coverage, domestic workers working abroad received more coverage than their local counterparts. Most importantly, Inquirer, Bulletin, and Star focused on the serious issues confronting the Filipina domestic workers."